Deterministic processes dominate microbial assembly mechanisms in the gut microbiota of cold-water fish between summer and winter - Xu, Liangliang; Xiang, Peng; Liu, Xiaoshuai; Zhao, Luying; Chen, Hanxi; Li, Maohua; Song, Zhaobin (Frontiers in Microbiology, 2024)
Exploring the effects of seasonal variation on gut microbiota of cold-water fish, plays an important role in understanding the relationship between seasonal variation and cold-water fish. Gut samples of cold-water fish and environmental samples between summer and winter were collected from the lower reaches of the Yalong River.The results of 16S rRNA sequencing showed that significant differences were identified in the composition and diversity of cold-water fish gut bacteria. Co-occurrences network complexity of cold-water fish gut bacteria increased from summer to winter (Sum: nodes: 256; edges: 20450; Win: nodes: 580; edges: 16725). Furthermore, the contribution of sediment bacteria (Sum: 5.3%; Win: 23.7%) decreased in cold-water fish gut bacteria, while the contribution of water bacteria (Sum: 0%; Win: 27.7%) increased from summer to winter. The normalized stochastic ratio (NST) and phylogenetic bin-based null model analysis (iCAMP) models showed that deterministic processes played a more important role than stochastic processes in the microbial assembly mechanism of cold-water fish gut bacteria. From summer to winter, gut bacteria community assembly mechanisms declined in the contribution of deterministic processes, while increased in the contribution of stochastic processes. Overall, these results demonstrated that seasonal variation influenced the gut bacteria of cold-water fish, and serves as a potential reference for future research to understand the adaptation of fishes to varying environments.